Control of Corruption, Regulatory Quality, Political Stability and Environmental Sustainability: A Cross-National Analysis - Sofik Handoyo; Fury Khristianty Fitriyah (Universitas Padjadjaran, 2018)
The study aims to reveal the correlation between governance attributes of the government and national environmental sustainability. The governance attributes of government in this study refer to the index of control of corruption, regulatory quality, and political stability. Meanwhile, national environmental sustainability refers to the index of national environmental performance. The period of investigation is the year of 2014 and involves 177 countries. Person correlation analysis was applied in this study to identify the degree of correlation between independent variables (control of corruption, regulatory quality, and political stability) dependent variable (environmental sustainability). Independent variables were measured using the World Governance Index (WGI) published by the World Bank. Environmental Performance Index (EPI) issued by The Yale Center for Environmental Law & Policy (YCELP) was proxied for measuring environmental sustainability. The results indicate that the state’s control of corruption, the national regulatory quality, and national political stability are positively associated with national environmental sustainability. The correlation coefficients are 0.230 (p<0.01), 0.193 ( p<0.01), and 0.167 ( p<0.01) respectively. Even though there is a positive correlation between public governance attributes and national environmental sustainability, however, the degree of correlation is weak. It implies that national governance is not a powerful instrument to predict national environmental sustainability.